Using speculation to enhance javascript performance in web applications - Martinsen, J. K.; Grahn, H.; Isberg, A. (IEEE internet computing, 2013)
JavaScript lets developers provide client-side interactivity in Web applications, but because it is sequential, it can't take advantage of multicore processors. Thread-level speculation (TLS) addresses this issue by enabling the speculation of JavaScript function calls and thus exploits the parallel performance potential multicore processors provide. The authors implemented TLS in the Squirrelfish JavaScript engine, which is part of the WebKit browser environment. They evaluate their approach using 15 popular Web applications on an eight-core computer, and show significant speed-ups without any modifications to the JavaScript source code.